Longitudinal measurement of fetal thigh soft tissue parameters and its role in the prediction of birth weight. (26th June 2013) - O'Connor, Clare; Farah, Nadine; O'Higgins, Amy; Segurado, Ricardo; Fitzpatrick, Chris; Turner, Michael J.; Stuart, Bernard; Kennelly, Máireád M.
ABSTRACT Objective The aim of this study was to profile longitudinal changes in thigh muscle and fat with gestation and to determine whether thigh measurements can improve the prediction of birth weight (BW). Methods A prospective longitudinal study of subcutaneous soft tissue measurements was conducted in 328 singleton fetuses at 28 and 37 weeks gestation. Estimated fetal weight (EFW) was calculated using abdominal circumference, femur length, biparietal diameter, and head circumference. Results The fetal abdominal subcutaneous tissue (FAST) and thigh muscle and fat show an increase with gestation. At 28 weeks gestation, the abdominal circumference, thigh fat, FAST, and EFW percentile were found to be significant predictors of BW. A combination of EFW percentile and thigh fat were found to be the optimal multivariate model at 28 weeks for predicting BW. At 37 weeks, BW prediction using EFW percentile, FAST, and thigh fat was the most accurate. The results revealed acceptable reproducibility for fetal thigh muscle and fat. Conclusion This study provides reference ranges for thigh fat and muscle at 28 and 37 weeks gestation. The inclusion of fetal thigh fat in the algorithm improves the predictive power for birth weight. This information is important to explore the role of fetal thigh in the detection of aberrant growth. © 2013 John Wiley & Sons, Ltd.